The Development of Creative Dance Based Anti Bullying Educational Media to Foster Children's Empathic Imagination in the Laboratory Kindergarten of Universitas Negeri Malang - Winda Istiandini; Wida Rahayuningtyas; Ari Wibowo Kurniawan (Jurnal Seni Tari, 2025)
The phenomenon of bullying in early childhood, especially among Generation Alpha who have minimal direct interaction, requires creative and interactive educational media to develop empathy. Although dance has proven to be effective in social development, the specific implementation of creative dance as an anti-bullying medium in Indonesia is still very limited. This study aims to develop and test the feasibility (validity and practicality) of creative dance-based anti-bullying educational media to foster empathic imagination in children in KB-TK Lab UM. This research uses a Research and Development (R&D) approach by adopting the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The product developed is in the form of a creative dance video with the song "Kita Teman Kita Hebat." The research subjects involved experts (materials, media, early childhood education) and 88 students of the UM Lab Kindergarten. The data was analyzed in a quantitative descriptive percentage. The results of expert validation show that the feasibility of the product is very high with an average of 90.47% (Very Valid). Meanwhile, the field trial recorded a practicality level of 89.85%. Dance art media facilitates children to imagine anti-bullying situations through movement and expression. This encourages the simultaneous development of cognitive and affective aspects of empathy. By dancing and playing, children learn to be aware of the differences in perspectives and feelings of friends, fostering mutual respect and solidarity. This medium is effective for strengthening the empathic imagination, a crucial skill to prevent bullying and support social-emotional development.